Histological Impairment of the Peripheral Nervous System in Diabetic Patients (Medical Forum Monthly, 2024)
Objective: To conduct a histological assessment of peripheral nerve injuries in 125 diabetic patients at Nowshera Medical College, focusing on evaluating nerve fiber density, myelination, axonal degeneration, and Schwann cell abnormalitiesStudy Design: A Cross-sectional observational Study.Place and Duration of Study: This study was conducted at the Department of Anatomy with the collaboration of Surgery Nowshera Medical College from October 2023 to March 2024.Methods: Hematoxylin and eosin staining, luxol fast blue staining, and toluidine blue staining were done on sural and radial nerve biopsies to quantify nerve fiber density and prompt myelin thickness and structural changes like axonal degeneration and Schwann cell abnormalities.Results: Among 125 diabetic patients aged 55. 4 (SD10. 2) years of age on average. The histological studies showed that the density of myelinated fibers was substantially reduced, demyelination was widely observed, and axonal loss was significantly elevated (p < 0. 05). Further histopathological abnormalities included the thickening of Schwann’s cells and formation of onion bulbs proving chronic neuropathy.Conclusion: Consistent with this, the study reveals the considerable histological affronts on (peripheral nervous system) PNS fibers in the affected diabetics, and as such, calls for early screening and management of the condition to prevent the devastating effects of diabetic neuropathy.